L’essenza del coaching. [The essence of coaching]. - Nicola Luigi Bragazzi; Giovanni Del Puente (Health Psychology Research, 2013)
Both Alessandro Pannitti and Franco Rossi have a solid and reputed experience of several years in the field of Coaching, and in this book they have provided the readers with their expert, authoritative overview on the different coaching techniques...